1991
DOI: 10.1016/0014-5793(91)80662-m
|View full text |Cite
|
Sign up to set email alerts
|

Characterization of trypsinogens 1 and 2 in two human pancreatic adenocarcinoma cell lines; CFPAC‐1 and CAPAN‐1

Abstract: Proteins with trypsin-like immunoreactivity (first detected by a specific immunoenzymatic assay) were isolated from CAPAN-1 and CFPAC-1 cell culture-conditioned media by chromatography on an immunoadsorbent prepared with a polyclonal antibody directed against trypsin 1. The adsorbed proteins were devoid of free trypsin activity but trypsin activity was present after enterokinase activation demonstrating that the immunoreactive trypsin present in cell supernatants corresponds to trypsinogens. When characterised… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
12
1

Year Published

1994
1994
2001
2001

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 20 publications
(13 citation statements)
references
References 25 publications
0
12
1
Order By: Relevance
“…Trypsinogen mRNA was detected in Capan‐1, AsPc‐1, MDAPanc‐3 and MDAPanc‐28 cells at different levels. Trypsinogen expression seems to be somewhat correlated with the invasive or metastatic potential of the cell lines [44]. The expression of a mixture of ductal, acinar and islet cell products in human pancreatic adenocarcinoma was reported previously by Kim et al .…”
Section: Discussionmentioning
confidence: 85%
“…Trypsinogen mRNA was detected in Capan‐1, AsPc‐1, MDAPanc‐3 and MDAPanc‐28 cells at different levels. Trypsinogen expression seems to be somewhat correlated with the invasive or metastatic potential of the cell lines [44]. The expression of a mixture of ductal, acinar and islet cell products in human pancreatic adenocarcinoma was reported previously by Kim et al .…”
Section: Discussionmentioning
confidence: 85%
“…Ductal phenotype marker such as carbonic anhydrase II was detected in some cell lines such as BxPC-3 but not in PANC-1 (36). Trypsinogens 1 and 2, which are markers for the acinar phenotype, were detected in CF-PAC-1 and CAPAN-1 cells but not in PANC-1 cells (37). In a previous study, we showed that human pancreatic tumoral cell lines BxPC-3 and SOJ-6 and human pancreatic adenocarcinoma tissue expressed a 46-kDa (p46) immunoform of BSDL, whereas the 100-kDa (p100) immunoform could not be detected in clarified cell extracts (22).…”
Section: Discussionmentioning
confidence: 94%
“…Because trypsinogen-2 and trypsin-2-AAT are better markers for pancreatitis than trypsinogen-1 Hedstriim et al, 1994), we wanted to evaluate their usefulness as markers for pancreatic cancer. Since tumor-associated trypsin-2 is expressed by various tumorcell lines (Koivunen et al, 1991;Miszczuk-Jamska et al, 1991) we also studied patients with other digestive-tract cancers. Patients with benign digestive-tract diseases were used as controls.…”
mentioning
confidence: 99%